The Role of Customer Experience Mediates the Effect of Service Quality and Price on Switching Intention in Bali Hotels - Gusti Ayu Wulandari; Gusti Ayu Agustina Riski; Ema Desia Prajitiasari (AIBPM Publisher, 2021)
This research aims to analyze service quality and price on customer experience and switching intention in hotel services in Bali. The study is an explanatory research about the influence of two independent variables service quality and price to the intervening variable customer experience, and its affect to switching intention as a dependent variable. Population and sampling using purposive sampling technique on 204 hotel customers in Bali. The primary data was taken from the questionnaire distribution and processed using the path analysis method. The results showed that the variables of service quality and price affect the customer experience of hotel service customers in Bali; service quality and customer experience variables affect switching intention in a negative direction, but the price variable can not influence the switching intention of hotel service users in Bali.